PERAN KECUKUPAN MODAL ATAS PENGARUH RISIKO PEMBIAYAAN DAN LIKUIDITAS TERHADAP PROFITABILITAS (STUDI PADA BANK UMUM SYARIAH PERIODE 2016-2018) - Ryan Yushinta; Muhammad Rusdi; Lidia Desiana (LA RIBA: Jurnal Perbankan Syariah, 2020)
This study aims to analyze and determine the influence of financing and liquidity risks on profitability with capital adequacy as an intervening variable in Islamic Commercial Banks in Indonesia for the period of 2016-2018. The population in this study were 14 Islamic Commercial Banks in Indonesia in the 2016-2018 period. The technique used in sampling is purposive sampling. The sample used is the 2016-2018 quarterly report on 7 Sharia Commercial Banks. The type of data used is secondary data. Data analysis techniques in this study used SPSS 21 software, which consisted of descriptive statistical analysis, classic assumption tests, multiple regression analysis, and mediation testing using the causal step and sobel test methods. By using multiple regression analysis, the results of the study show that the financing risk (NPF) has a negative and significant effect on profitability (ROA). Liquidity (FDR) has a positive and significant effect on profitability (ROA). Capital adequacy (CAR) doesn???t affect profitability (ROA). Financing risk (NPF) has a negative and significant effect on capital adequacy (CAR). Liquidity (FDR) doesn???t affect capital adequacy (CAR). Then based on the results of the analysis using the causal step and sobel test methods, capital adequacy (CAR) mediates the effect of financing risk (NPF) and liquidity (FDR) on profitability (ROA).